A Case of Adrenal Histoplasmosis (BIRDEM Medical Journal, 2017)
Histoplasmosis is a fungal disease that may present as chronic pulmonary infection or in disseminated form. Disseminated histoplasmosis frequently affects the adrenal gland; sometimes adrenal gland may be the only site of demonstrable disease. Unilateral involvement in immunosuppressed patients is the usual presentation but bilateral involvement may be also there. Early diagnosis and treatment may save the patient from catastrophic adrenal insufficiency. Considering the risk of morbidity following adrenal insufficiency and the wide availability of effective treatments, adrenal histoplasmosis must be considered in adults who had adrenal masses. Though asymptomatic adrenal involvement has been described in patients with disseminated histoplasmosis; isolated adrenal involvement with or without adrenal insufficiency as the presenting feature of the disease is rare. In this report, a 42 years male presenting with history of weight loss, fever and later revealed bilateral adrenal mass, who was successfully treated with antifungal drug is described.Birdem Med J 2018; 8(1): 77-80